Thiol redox control via thioredoxin and glutaredoxin systems. (26th October 2005) - Holmgren, A.; Johansson, C.; Berndt, C.; Lönn, M.E.; Hudemann, C.; Lillig, C.H.
Abstract : The Trx (thioredoxin) and Grx (glutaredoxin) systems control cellular redox potential, keeping a reducing thiol-rich intracellular state, which on generation of reactive oxygen species signals through thiol redox control mechanisms. Here, we give a brief overview of the human Trx and Grx systems. The main part focuses on our current knowledge about mitochondrial Grx2, which facilitates mitochondrial redox homoeostasis during oxidative stress-induced apoptosis.